Public Space Visitor’s Behaviors with the Use of Mobile Phone Features: Case study in Losari Beach Platform Makassar City, Indonesia - Mukti Ali (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2013)
Research focused on the intersection two aspects of people interaction and communication activities in public spaces and people's behavior in using mobile phones with the case in Losari beach platform. Losari beach is one of the crowded public spaces and an icon of Makassar. Research objectives are determine characteristic of mobile phone use by age and gender, relationship between mobile phone features behavior and mobile phone physical behavior in public space. This research uses observation and questionnaires method to find mobile phone behavior and features data in public space. The findings are the visitors who use mobile phone dominated adult with male more than female except in session 3 (17:00-19:00) the number of female more than male, the main functions of mobile phone for sms/mms and calling has change into camera function, and the mobile phone behavior tends to be dynamic and active in Losari beach platform.